Maimendong Decoction Improves Pulmonary Function in Rats With Idiopathic Pulmonary Fibrosis by Inhibiting Endoplasmic Reticulum Stress in AECIIs - Shen, Mengmeng; Nan, Yanan; Zhang, Lan; Di, Liming; He, Shuangshuang; Li, Yu; Li, Yadong (Frontiers in Pharmacology, 2020)
This study was designed to investigate the mechanism by which MMDD improves lung function, and observe the effect of MMDD on endoplasmic reticulum stress(ERS) in alveolar type II epithelial cells (AECIIs) of pulmonary fibrosis rats. pulmonary fibrosis animal model was established by intratracheal injection of BLM at a dose of 6mg/kg body weight. Overall, Thirty male SPF Sprague-Dawley rats were randomly divided into control group, BLM group and BLM+MMDD group. BLM+MMDD group rats were fed 24g/kg over three weeks for twice a day on the fourteenth day after model establishment. MMDD improves pulmonary function of fibrotic rats and reduces the occurrence of endoplasmic reticulum stress in AECIIs. MMDD could significantly improve the forced vital capacity (FVC) of bleomycin-induced pulmonary fibrosis in rats. MMDD reduced the expression of GRP78 and CHOP in AECIIs, increased the secretion of surface active protein C (SPC) by AECIIs. Moreover, the apoptosis of the fibrosis zone in the lung tissue was remarkably mitigated by administration of MMDD. The finding of this study revealed that MMDD can improve lung function in rats with pulmonary fibrosis by reducing the occurrence of ERS and cell apoptosis of AECIIs. It may provide a new method for the treatment of pulmonary fibrosis.